The Effect of the Group Investigation Model Assisted by the “Make a Match” Game on Mathematical Problem-Solving Ability in Statistics - Armina Rangkuti; Isran Rasyid Karo-Karo (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
This study aimed to examine the effect of the Cooperative Learning model of the Group Investigation (GI) type assisted by the Make a Match game on students’ mathematical problem-solving ability in statistics. The study employed a quantitative approach with a quasi-experimental method and a Nonequivalent Control Group Design. The sample consisted of 53 eighth-grade students, with 27 students in the experimental group and 26 students in the control group. Data were collected using an essay test of mathematical problem-solving ability that met the validity and reliability requirements (r₁₁ = 0.930). The data were analyzed using descriptive statistics, the Lilliefors normality test, the homogeneity test, an independent-samples t-test, and Cohen’s d effect size. The results showed that the mean posttest score of the experimental class was 83.78, compared with 78.96 for the control class. The t-test result showed a t-count of 2.190, which was greater than the t-table value of 2.008 at α = 0.05, indicating a significant difference between the two groups. The Cohen’s d value of 0.60 indicated a medium effect. Therefore, the Cooperative Learning model of the Group Investigation type assisted by the Make a Match game had a significant and practically meaningful effect on students’ mathematical problem-solving ability in statistics.